On the nature of intermediary relations in insurance - P.Z. Ivanishin (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the problems associated with the activity of insurance intermediaries, the legal capacity of insurance agents and brokers with regard to meeting licensing requirements, the relation between the agency contract and the guarantee contract for the purposes of insurance, as well as the place and role of the insurance broker in the legal relations under study. It also provides a classification of the intermediary relations in insurance and defines its criteria. Based on the results obtained, the conclusion is made that the insurance agent acting for and on behalf of the insurer can perform the following physical actions in addition to the legally significant ones, i.e., concluding insurance contracts: searching for and bringing in new clients, negotiating, arranging and justifying the calculation of an insurance premium, and involving clients in partner-intermediary relations of the insurer. The analysis of the legal nature of the insurance broker as against the insurance agent shows that the criteria for differentiation include both legal features, such as legal capacity, and particular contractual constructions. The insurance broker acting for the benefit of the insurer acquires intermediary functions on the basis of mandate or commission agreements, agency agreements, or paid services agreements. All actions of the insurance broker in the interests of the insurer (reinsurer) are specified by paid services agreements because the insurance broker becomes an actual agent of the insurer in exercising their obligations to genuinely represent the interests of the insurer under the agency agreement, mandate or commission agreements, which is expressly prohibited by law. The detailed survey of the multi-level models of intermediary-partnership relations, in which several entities become involved in the intermediary relations, reveals that confusion can be avoided by recognizing the sub-agent or sub-broker relations at the regulatory level.